2017
DOI: 10.30539/iraqijvm.v41i1.73
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of the Newcastle disease virus from field outbreaks in broiler and layer flocks in Iraq

Abstract:      Newcastle disease is one of serious pathological problems and causes of vast economic losses during 2011-2016 in Iraq. The disease caused high mortalities in all types of poultry nevertheless of vaccination. In this study all samples were collected from infected flocks with clinical signs of the disease. Inoculation of chicken embryonated eggs was carried out for virus isolation, identification, Haemagglutination and Haemagglutination Inhibition assay. Using Reverse Transcriptase-Polymerase Chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…Group 5 which showed opposite results because birds were not vaccinated and not protected against NDV and these results went with (16). Also Group 4 shows opposite results Due to the mycotoxins toxic effects, which is in agreement with (10).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Group 5 which showed opposite results because birds were not vaccinated and not protected against NDV and these results went with (16). Also Group 4 shows opposite results Due to the mycotoxins toxic effects, which is in agreement with (10).…”
Section: Discussionsupporting
confidence: 86%
“…Immune response in G1 was better than G2 the results were consistent with (10), who demonstrated that the immunogenicity of the live vaccine was a cellular immunity primarily dependent on Cytokines and its role in stimulating many defense cells against infectious antigens, While the vaccination with killed vaccines stimulating Humoral immunity, which relies on the stimulation of B cells that produce Ab according to amount of Ag in the killed vaccine without reliance on other defense cells, which explains the slow immunity available from the killed vaccines. The reason of increase in immune response in G5 after challenge virulent local isolate of ND, return to not vaccinated against ND to protect the chicks from infection, These results agreed with (16), who proved that the chicks were exposed to NDV infection in the third week after decline the maternal immunity and highly increase of Abs with high mortality in chicks due to acute infection. But the low Ab titre in G4 return to toxic effect of mycotoxin these results agree with (4) show that mycotoxins damage the proteins found in cell junctions and thus reduce the transmission of electrical impulses, that transfer of cytokines between immune cells.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The respiratory and digestive tracts of birds are part of their mucosal immune system. While parenterally delivered vaccinations mainly trigger systemic reactions, mucosal immunization promotes mucosal immune responses with S-IgA antibody as well as systemic humoral and cellular immunological responses (17,29). When compared to other vaccination methods, mucosal delivery offers a number of benefits, including a wide epithelial surface with a lot of microvilli, a porous endothelium membrane, a highly vascularized mucosa that facilitates absorption, and ready accessibility (28).…”
Section: Local Immunity Detection (Iga)mentioning
confidence: 99%